Spatial distribution and risk assessment of fluorine and cadmium in rice, corn, and wheat grains in most karst regions of Guizhou province, China - Li, Xiangxiang; Zhou, Luoxiong; Zhang, Cheng; Li, Dasuan; Wang, Zelan; Sun, Dali; Liao, Chaoxuan; Zhang, Qinghai (Frontiers in Nutrition, 2022)
The pollution status of crops planted in Guizhou province of Southwestern China with high background values of Fluorine (F) and Cadmium (Cd) has attracted people’s concern. The present study aimed to investigate the spatial distributions of F and Cd in rice, corn and wheat grains, and further evaluate their health risks to residents in Guizhou province. The contents of F and Cd were measured by fluoride ion-selective electrode and inductively coupled plasma mass spectrometry (ICP-MS) methods, respectively. Additionally, the inverse distance weighted (IDW) technique was conducted to analyze spatial distribution, and the health risk was estimated by target hazard quotient (THQ) and hazardous index (HI). The results indicate that Cd contents in samples varied from 0.000 to 0.463 for rice, 0.000 to 0.307 for corn and 0.012 to 0.537 (mg/kg) for wheat, while F contents ranged from 0.825 to 5.193 (rice), 0.946 to 8.485 (corn) and 0.271 to 9.143 (wheat) mg/kg. The Cd exceeding ratios were 11.600% for rice, 13.500% for corn, and 45.100% for wheat grains, respectively. In terms of spatial distribution, high levels of F and Cd in rice were found in the northern and central in Guizhou, while Cd in corn was distributed in the eastern and F in corn were distributed in the west area of Guizhou. Moreover, the high levels of F and Cd in wheat were distributed in the western and eastern areas. The mean carcinogenic risks (R) of Cd in rice, corn, and wheat in children were 4.150 × 10-4, 1.670 × 10-4 and 3.470 × 10-4, respectively, and that in adults were 3.430 × 10-4, 0.471 × 10-4 and 2.190 × 10-4, respectively. The HI for adults in rice, corn and wheat grains were 0.756, 0.154 and 0.514, respectively, and that for children were 0.913, 0.549 and 0.814, respectively. Collectively, the potential risks produced by F and Cd to the local residents should not be ignored.